Simultaneous tree stem and soil greenhouse gas (CO2 , CH4 , N2 O) flux measurements a novel design for continuous monitoring towards improving flux estimates and temporal resolution - Bréchet, Laëtitia M (The New phytologist, 2021)
© 2021 The Authors New Phytologist © 2021 New Phytologist Foundation.